STRUCTURAL SYSTEM SIMULATION USING GRID-COMPUTING FRAMEWORK - Data Iranata; Radityo Anggoro (Institut Teknologi Sepuluh Nopember, 2009)
A multi-level modeling and simulation method of structural system using grid-computing framework is proposed in this paper. Two levels of parallel processing will be involved in this framework: (1) multiple locally distributed computing environments connected by the local network to form (2) a grid-based cluster-to-cluster distributed computing environment. To successfully perform the simulations, a large-scale structural system is decomposed into the simulations of a simplified global model and several detailed component models with various scales. These correlated multi-scale simulation tasks are distributed amongst clusters and connected together in a multi-level modeling and simulation method and then coordinated over the internet. This paper also presents the development of a grid-computing software framework that can support the proposed simulation approach. The architectural design of the program also allows the integration of several multi-scale models to be clients and servers under a single platform. Additionally, the comparison result between proposed method and assumed exact solution show that the proposed simulation method is appropriate to simulate the response of the structural systems.